PELAKSANAAN PENGAJARAN DAN PEMBELAJARAN KURSUS PENGAJIAN MALAYSIA: KAJIAN TINJAUAN DI UNIVERSITI ISLAM ANTARA BANGSA SELANGOR - Hairol Anuar Hj Mak Din; Khairul Hamimah Mohd Jodi; Faridah Che Hussain (Jurnal Community, 2017)
The Malaysia  Education Blueprint 2015-2025 clearly shows the aspirations of the Higher Education Ministry on the importance of applying national identity among graduates at Higher Education Institutions. In line with the wishes, the course of Malaysia Studies is a major medium for the building of patriotism values among students. Hence, the Malaysian Studies Course was strengthened and used as one of the General Subjects (MPUs) conducted by all Institutions of Higher Learning. All citizens and non-citizens are required to attend and pass the Malaysian Studies Course as a graduation requirement. In order to make the course more interesting and interactive, the Teaching And Learning method is always improved to achieve the predetermined learning outcomes. Thus, a study using a quantitative approach has been undertaken to identify students' responses to the implementation of the Malaysian School of Excellence in KUIS. The Teaching And Learning implementation assessment for this course is based on scoring components, teaching staff and teaching aids. The findings show that Teaching And Learning implemented in Malaysian Studies courses is relevant and capable of applying the elements of identity and patriotism among students. Keywords: Teaching And Learning, General Studies subjects, Malaysian Studies Course